Experimental Research on Different Types of Underground Heat Exchangers - 李新国; 薛玉伟; 赵军 (Zhileng xuebao)
The experiments on different underground exchangers were carried out to research their exchange performance. The experimental datum on heat extraction and heat rejection of single U and double U models vertical underground pipes was analyzed using heat exchange capacity of unit pipe. The conclusion is that single U models vertical underground pipes is better than double U models. The influence of the flux and the temperature on exchange performance was investigated. The results show that the heat exchange capacity increase when the flux increase; The heat rejection increase and heat extraction decrease when the temperature increase.